2011
DOI: 10.1089/jpm.2010.0471
|View full text |Cite
|
Sign up to set email alerts
|

Staff Perceptions of End-of-Life Care in Aged Residential Care: A New Zealand Perspective

Abstract: A response rate of 32% was obtained. Respondents indicated a relatively high level of confidence regarding their care of the dying, including aspects of communication, teamwork and use of documentation. However, this was often contradicted by their written responses. Written comments were analyzed thematically and six themes identified: the naturalness of dying; the character of care; care relationships; emotional response; knowledge; and the organizational environment. Data analysis provided a rich and inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
1
26
0
4
Order By: Relevance
“…For more than a decade, researchers have documented the challenges and barriers to providing a palliative approach to older people in ARC 3 6 16 23. What is required now are actions that address these challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more than a decade, researchers have documented the challenges and barriers to providing a palliative approach to older people in ARC 3 6 16 23. What is required now are actions that address these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…ARC mortality in New Zealand is high 12. A prospective follow-up study of 6828 ARC residents in 152 facilities reported that 861 residents (12.6%) had died within 6 months of ARC entry 16. Indeed, ARC facilities in New Zealand have been characterised as ‘de facto hospices’, in contrast with their previous role as rehabilitation centres 6…”
Section: The New Zealand Contextmentioning
confidence: 99%
“…41 Previous research has also examined selfconfidence as both motivator and outcome of palliative care education. [42][43][44] The current research goes further to explore the predictive value of both socioenvironmental and psychological factors. The regression results indicate the need for a better understanding of burnout among RAC healthcare staff.…”
Section: Discussionmentioning
confidence: 99%
“…37,43,51 Previous research has also highlighted the communication environment as a key component in providing effective palliative care. 52,53 Drawing on complexity science (In complexity science healthcare organizations, including aged care facilities, are defined as complex adaptive systems (CAS).…”
Section: Discussionmentioning
confidence: 99%
“…"(…) at the start it was hard on me (…) because I had to train, I wasn't trained yet (…)" E1. In the study by Marshall et al 27 , the team describes how certain members avoid caring for elderly persons at the end of life, citing a lack of knowledge and experience in the area. For this reason, it may be difficult for them to deal with elderly persons in terminal situations, which was also mentioned by the professional caregivers in the present study.…”
Section: Negative Experiences and Feelingsmentioning
confidence: 99%